Theoretical Aspects Of Researching Agricultural Geography (Texas Journal of Multidisciplinary Studies, 2025)
The article analyzes the theoretical and methodological foundations of the study of agricultural geography. The "center-periphery" model, economic integration, efficient use of resources, and principles of environmental sustainability are covered. The research results show the importance of an integrated approach of economic, geographical and environmental factors in the development of agriculture.